Clarification and criticism of Iraqi researcher's point of view about real credits - NasrAzadani MohammadJavad; Ahmad Abedi (حکمت اسرا)
The discussion of credits is one of the important topics that can be the source of works in various sciences, including jurisprudence and principles. The truth of credits and credit matters, types of credits and the relationship between credits and reality are important issues that must be addressed in the topic of credits. Many thinkers such as the late Esfahani and Allameh Tabatabaei have discussed the mentioned issues appropriately. Iraqi researcher is also among the thinkers who raised this debate in his fundamental discussions. From the Iraqi researcher's point of view, credits are divided into two categories, which are pure credits and real credits. He believes that real credits are appointed and become reality after the credit in the external world.His main reason for this is the survival of such credits with the assumption of creditors. His statement is flawed in many ways, and the most important flaw is that the idea that cedits such as property, after the extinction of creditors, still remain. it is not correct, because the creditors of stewardship of the property is intellectuals, and it is certain that if all intellectuals are destroyed, it will not remain and there will be no place to assume property.